3D GIS: the state-of-the art - Abdul Rahman, Alias (Jawatankuasa Pemetaan dan Data Spatial Negara, 2002)
An increasing number of applications need advanced 3D tools for representing and analysing real world. At present, many software packages can handle a wide range of spatial problems. However, is the functional 3D GIS already a reality? This paper tries to find the answer by analysing both software available and efforts of researchers. An overview of several commercial systems and a 3D case study provide knowledge about 3D functionality offered in the market. The most significant achievements in the 3D research area concerning 3D structuring and 3D topology portray the current research status and delineate new research topics.